2021
DOI: 10.3390/cells10113219
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Tumoral Potential of Phosphonate Analog of Sulforaphane in Zebrafish Xenograft Model

Abstract: Isothiocyanates (ITCs) show strong activity against numerous human tumors. Five structurally diverse ITCs were tested in vivo using the zebrafish embryos 6 and 48 h post-fertilization (hpf). The survival rate, hatching time, and gross morphological changes were assessed 24, 48, and 72 h after treatment with all compounds in various doses (1–10 µM). As a result, we selected a phosphonate analog of sulforaphane (P-ITC; 1–3 µM) as a non-toxic treatment for zebrafish embryos, both 6 and 48 hpf. Furthermore, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…18 , 19 , and 36 : these were found to manifest strong affinity to ALDH isoforms and ABC proteins based on in silico analysis. Interestingly, 18 and 19 have also presented strong anti-tumoral properties in a xenograft zebrafish model [ 83 ]. The chosen ITCs appear to be strong anti-cisplatin-resistance agents: they were found to significantly repress cisplatin tolerance in both A549CisR and in the stage 4 NSCLC cell line NCI-H1581 at concentrations 10-fold lower than DSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 , 19 , and 36 : these were found to manifest strong affinity to ALDH isoforms and ABC proteins based on in silico analysis. Interestingly, 18 and 19 have also presented strong anti-tumoral properties in a xenograft zebrafish model [ 83 ]. The chosen ITCs appear to be strong anti-cisplatin-resistance agents: they were found to significantly repress cisplatin tolerance in both A549CisR and in the stage 4 NSCLC cell line NCI-H1581 at concentrations 10-fold lower than DSF.…”
Section: Discussionmentioning
confidence: 99%
“…ITCs have also been found to be effective against a murine mammary gland carcinoma 4T1 model in vivo, with administration resulting in reduced tumor mass [ 33 ]. Furthermore, 3 µM ITC analogs inhibited the motility of three highly malignant cell lines derived from cervical (HeLa), glioblastoma (U87), and breast (MDA-MB-231) carcinomas [ 83 ]. This finding is consistent with our present observations.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies of the selected P-ITCs showed slightly lower anticancer and antimetastatic activity in comparison to naturally occurring BITC. However, recent studies in vivo on Zebrafish have shown that P-SFN 291 was characterized by high anticancer activity and low toxicity [ 256 ].…”
Section: Synthesis Of Bifunctional Analogs Of Sulforaphane and Their ...mentioning
confidence: 99%
“…The optical clarity of the zebrafish ( Danio rerio ) model makes it uniquely suited for the study of TNLMD as it enables microinjection of cancer cells into LMD-associated anatomical structures while allowing simultaneous fluorescent monitoring of cell proliferation and migration [ 12 , 13 ]. A major advantage of zebrafish xenograft models over rodent models is the availability of pigment-deficient strains, e.g., casper ( roy -/-; nacre -/-), that allow observation of transplanted cancer cells, and the absence until 4–6 weeks after fertilization of an adaptive immune system that could reject foreign implanted cells [ 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microinjection of fluorescent rhodamine dye into the CSF of the hindbrain ventricle permits microscopic visualization and analysis of the developing zebrafish ventricular system [ 16 , 17 , 18 ]. Researchers have microinjected glioblastoma cells labeled with the red fluorescent dye 1,1′-dioctadecyl-3,3,3′,3′-tetramethylindocarbocyanine (DiI) into the zebrafish hindbrain ventricle and assessed cancer cell proliferation and migration using bright-field and fluorescent microscopy, and analyzed glioblastoma response to the phosphoinositide 3-kinase inhibitor LY294002, zinc oxide nanoparticles, and isothiocyanate derivatives [ 12 , 13 ]. In addition, transplantation of zebrafish brain tumor cells into the fourth ventricle resulted in LMD along the spinal cord in a subset of recipients [ 19 ].…”
Section: Introductionmentioning
confidence: 99%